PENGARUH PENYALURAN DANA KUR (KREDIT USAHA RAKYAT) TERHADAP PENDAPATAN UMKM MASYARAKAT DI JORONG SALIDO BARAT NAGARI SALIDO SAROHA KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Delfia Nora; Septria Susanti (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to find out whether the distribution of People’s Business Credit Funds (KUR) has an effect on the income of community MSMEs in Jorong Salido Barat. Data collection uses primary data. The population of this research is the community of MSME owners who borrowed KUR funds in Jorong Salido Barat, totaling 34 people. The sampling technique in this research is Saturated sampling, which is a sampling technique if all members of the population are used as samples. This is often done when the population is relatively small, less than 30 people, so all members of the population are sampled, namely 34 people. Data analysis methods include Research Instrument Tests through Validity and Reliability Tests, Classical Assumption Tests through Normality Tests and Heteroscedasticity Tests, Simple Linear Regression Analysis, hypothesis testing through T Tests (Partial) and Determination Coefficient Tests (R2). The results of this research show that in the Correlation test (T test) the significant value of tcount > ttable is 10.289 > 1.693. This shows that the more People’s Business Credit (KUR) given to MSME owners can be put to good use by Micro Business actors for business capital, the more they can increase their income.